The Synergistic Effect of Aqueous Extracts of Iraqi Propolis and CPP-ACPF Paste on Enamel Microhardness after Demineralization Challenge - Mayada Kashmoola; Aisha A. Qasim (University of Mosul, College of Dentistry, 2021)
Aims: This study endeavors to estimate the synergistic effect of aqueous extracts of propolis on microhard-ness power of fluoridated CPP-ACP (MI plus) paste after demineralization challenge. Materials and methods: A total of (75) posterior wisdom teeth were used in the study. Enamel blocks were prepared and divided into five groups randomly, the teeth in all groups were subjected to demineralization cycle and then treated with: Sinjar's aqueous extract of propolis (AEP) -MI paste plus cream n. (15), Sulaymaniah's AEP-MI paste plus cream n. (15), Duhok's AEP-MI paste plus cream group n. (15), control positive group of MI paste plus alone n. (15), and control negative group of artificial saliva alone n. (15). Microhardness of enamel blocks was measured using Vickers microhardness tester machine at base line, after demineralization cycle and finally after treatment protocol. Results: Statistically, there were highly significant differences among study groups after demineralization cycle and there was a decrease in surface microhardness in all groups after demineralization, but the least reduction in surface microhardness belonged to mixture of Sulaymaniah's aqueous extract of propolis with MI paste plus followed by MI paste plus alone group after treatment proto-col. Conclusions: Mixture of Sulaymaniah's aqueous extract of propolis with MI paste plus was significantly better than MI past plus alone in preserving enamel's hardness and resisting the demineralization challenge.